2006
DOI: 10.1111/j.0909-752x.2006.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of acid‐ and alkaline‐treated human dermis: a correlation between total surface charge and elastic modulus

Abstract: It is proposed that the pH and charged residue dependency of the elastic modulus suggests that charged pair interactions and repulsions within and between collagen molecules are involved in elastic energy storage during stretching at high strains. It is hypothesized that elastic energy storage is associated with the stretching of pairs of charged amino acid residues that are found primarily in the flexible regions of collagen molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 18 publications
3
38
0
1
Order By: Relevance
“…Changes in the number of glutamic acid, threonine, serine, and threonine residues could cause changes in the surface charge of collagen molecules (49,53), whereas changes in the quantity of valine, alanine, and phenylalanine residues could infl uence the level of collagen helix rigidity (49). In addition, changes in glycine residues could affect the number of Arg-GlyAsp domains responsible for the processes of cell adhesion to collagen structures (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the number of glutamic acid, threonine, serine, and threonine residues could cause changes in the surface charge of collagen molecules (49,53), whereas changes in the quantity of valine, alanine, and phenylalanine residues could infl uence the level of collagen helix rigidity (49). In addition, changes in glycine residues could affect the number of Arg-GlyAsp domains responsible for the processes of cell adhesion to collagen structures (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, stress-strain protocols reveal that soft tissues may be characterized by a history-independent elastic component and a history-dependent viscous component (137,407,420,421). Under certain conditions, a straindependent plastic component can also be revealed.…”
Section: Basic Spring and Dashpot Constitutive Equationsmentioning
confidence: 97%
“…Although the only stress information obtained from an instantaneous strain-step are the initial and final values, this, along with the subsequent stress relaxation to steady state, are sufficient when applying a sequential series of stretch strain-step/strain-clamps over a long strain-range to separate the stress response into elastic and viscous components ( Fig. 13) for tissues such as artery, vein (420,421), and skin (407).…”
Section: Basic Spring and Dashpot Constitutive Equationsmentioning
confidence: 99%
“…Human decellularized dermis was obtained from allograft tissue as described previously 5,6,[9][10][11] (Table 1). Decellularized human dermal samples were tested after immersion in phosphate buffer solution as described elsewhere.…”
Section: Sample Preparationmentioning
confidence: 99%
“…5,6,[9][10][11] Recently we have reported the use of optical coherence tomography (OCT) and vibrational analysis to non-invasively and non-destructively measure the mechanical properties of decellularized human dermis in vitro 5,6 and human skin in vivo 12 this technique measures the resonant frequency of a tissue or polymer and then converts the resonant frequency into a modulus. In addition, we have reported that moduli measurements made at the resonant frequency of ECMs and silicone rubber are quasi-elastic, since the viscous contribution to the mechanical behavior is as low as 2% to 4%.…”
Section: Introductionmentioning
confidence: 99%